EFFECT ANALYSIS OF FDI, EXPORTS, EXCHANGE RATES, ON INDONESIA'S ECONOMIC GROWTH 1991-2020 - Erika; Sasana, Hadi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
The purpose of this study is to examine the impact of foreign direct investment (FDI), exports, and the exchange rate on Indonesia's economic growth from 1995 through 2020. This research is quantitative descriptive in nature. The study employs time series data and eviews for testing. Economic growth is the dependent variable, whereas foreign direct investment (FDI), exports, and exchange rates are the independent factors. This study employs Autoregressive Distributed Lag (ARDL) regression, and a long-term and short-term association is present. Foreign Capital Investment (FDI) is the dominant factor that affects economic growth and is not significant using = 5, while the relative export variable has a significant positive effect on economic growth, and the exchange rate variable affects economic growth positively but is not statistically significant.